Altered lipid metabolism in gastroschisis: A novel hypothesis. Issue 8 (21st June 2013) - Jones, Kenneth Lyons; Weiss, Lauren A.; Hagey, Lee R.; Gonzalez, Vanessa; Benirschke, Kurt; Chambers, Christina D.
Abstract Gastroschisis is a congenital abdominal wall defect where there is herniation of abdominal organs. Optimal maternal nutritional intake, in particular, fatty acids, are vital for proper growth and development of the fetus. This pilot case–control study explored the association of several biomarkers of fatty acids and gastroschisis. Between 2008 and 2011, we recruited 13 pregnant women in mid‐gestation who were referred to the UCSD Prenatal Center for evaluation of an abnormal maternal serum alpha‐fetoprotein (MSAFP) test and subsequently identified as carrying a baby with gastroschisis. Nine controls were selected from a false positive MSAFP or from the UCSD prenatal clinic. At enrollment, maternal blood was drawn for analysis of fatty acids. Mann–Whitney–Wilcoxon tests were used to test for mean differences between erythrocyte fatty acid biomarkers and the fatty acid lipogenic (palmitic acid: linoleic acid) and desaturation (palmitoleic acid: palmitic acid) indices and gastroschisis. Mothers carrying a baby with gastroschisis and gastroschisis babies had consistently higher levels of palmitoleic acid (all P's < 0.05), gastroschisis mothers had lower levels of oleic acid during pregnancy and at delivery, and higher levels of DHA at delivery (all P's < 0.05). The lipogenic index was significantly lower at delivery for gastroschisis mothers (P < 0.05) and the desaturation index was consistently higher in gastroschisis mothers and babies (all P's < 0.01). These findings suggest that early maternal inflammation possibly resulting from an imbalance of fatty acids, leading to a vascular disruption, may be the underlying mechanism responsible for at least some cases of gastroschisis. © 2013 Wiley Periodicals, Inc.